Mechanics of Biological Systems and Materials, Volume 4 Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics - Barthelat, Francois; Zavattieri, Pablo; Korach, Chad S; Prorok, Barton C; Grande-Allen, K. Jane (Conference Proceedings of the Society for Experimental Mechanics Series,, 2014)
Mechanics of Biological Systems and Materials, Volume 4: Proceedings of the 2013 Annual Conference on Experimental and Applied Mechanics, the fourth volume of eight from the Conference, brings together contributions to this important area of research and engineering.Â  The collection presents early findings and case studies on a wide range of areas, including: Â  Structure-Function & Design of Soft Biological Tissues Soft Tissue Biomechanics: Nanoscale to Physiological Control Bone Mechanics Biomimetic Materials Residual Stresses in Biological Materials Cells Cellulose Materials.